Confirmed Detection of Lithium in Nearby Young Late-M Dwarfs - Ngoc, Phan Bao; Bessell, Michael S. (Communications in Physics, 2022)
Brown dwarfs in nearby young associations and moving groups are excellent benchmarks for studyingphysical properties of these substellar objects at different ages as well as their formation mechanism.In our previous search for nearby young brown dwarfs, we reported the first clear detection of the lithium absorption line in three late-M dwarfs and a marginal detection in one late-M dwarf.Based on our new spectroscopic observations, we confirm our previous detection of lithium inthe four late-M dwarfs. We also confirm the presence of lithium in one brown dwarf binary that haspreviously been reported in the literature. Using theoretical models, we estimate the age and the mass of these late-M dwarfs. We then use a Bayesian analysis tool for determining the membership probability of these young late-M dwarfs to nearby young moving groups.